Pasteurella multocida and immune cells - Hieke-Kubatzky, Katharina (Pasteurella multocida, 2012)
Pasteurella multocida was first discovered by Perroncito in 1878 and named after Louis Pasteur who first isolated and described this Gram-negative bacterium as the cause of fowl disease in 1880. Subsequently, P. multocida was also found to cause atrophic rhinitis in pigs, haemorrhagic septicaemia in cattle and respiratory diseases in many other animals. Among other factors such as lipopolysaccharide, outer membrane proteins and its capsule, the protein toxin (PMT) of P. multocida is an important virulence factor that determines the immunological response of the host’s immune system. However, the exact molecular mechanisms taking place in cells of the innate and adaptive immune system are largely unknown for any of these virulence factors. Due to the obvious function of PMT on cells of the porcine skeletal system where it causes bone destruction, PMT was regarded as an osteolytic protein toxin. However, it remained unclear what the actual benefit for the bacteria would be. Recently, more attention was drawn to the osteoimmunological effects of PMT and the interplay between bone and immune cells. This review summarises the knowledge of effects of P. multocida virulence factors on the host’s immune system.
Gesehen am 26.10.2018